Yeast and Fertility : Effects of In Vitro Activity of Candida spp. on Sperm Quality (2018)
ABSTRACT: Background: Candida spp. causes semen candidiasis, the most important sexually transmitted fungal infection; this microorganism affects male fertility potential and could alter oocyte fertilization. The in vitro effects of the yeasts Candida albicans and Candida glabrata and their soluble factors of fungal metabolism on semen quality were studied. Methods: Candida strains (2, 0.5 and 0.05 McF) and their soluble factors were incubated for 3 hr with selected spermatozoa. Conventional (Viability and motility) and functional parameters (Mitochondrial membrane potential, membrane integrity, detection of reactive oxygen species and DNA fragmentation) were quantified in 35 semen samples. In addition, human spermatozoa were incubated under capacitating conditions with Candida spp. and soluble factors. Finally, spermatozoa were incu- bated with mannose before incubation with either yeast to block sperm and yeast interaction. Data was analyzed using Friedman test, and p<0.05 was considered significant. Results: The conventional sperm parameters were statistically affected by the two yeast strains after 3 hr and their effect was maintained until the 24 hr incubation. However, the functional parameters were altered, this change was not statistically significant. Pretreatment of spermatozoa with mannose decreased the effect of Candida spp. Conclusion: The presence of C. albicans or C. glabrata affects seminal parameters. The effect is related to incubation time and yeast concentration, it can be supposed that the yeast sperm interaction is mediated through the mannose sperm receptor.